2016
DOI: 10.5535/arm.2016.40.4.710
|View full text |Cite|
|
Sign up to set email alerts
|

Proposal and Evaluation of a Telerehabilitation Platform Designed for Patients With Partial Rotator Cuff Tears: A Preliminary Study

Abstract: ObjectiveTo propose and evaluate the effectiveness of a telerehabilitation platform designed for patients with rotator cuff (RC) tears.MethodsDuring the first study phase, a virtual service platform that included information on RC tear pathology, joint care, and a series of instructions regarding therapeutic exercise was designed and created. Subsequently, in the clinical phase, a quasi-experimental study was performed. The platform was tested on patients and evaluated at baseline and at 1, 2, 3, and 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 26 publications
0
44
0
1
Order By: Relevance
“…Physical therapy by means of telehealth has been shown to be a viable option for improving knee osteoarthritis symptoms and leg strength . Telehealth has also been investigated by means of a pilot study for physical therapy for partial rotator cuff injury . Other studies have looked at telehealth in follow‐up after joint arthroplasty and following fractures and found that overall home telehealth is at least as effective as usual care .…”
Section: Specific Telehealth Applications For Neuromuscular or Musculmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical therapy by means of telehealth has been shown to be a viable option for improving knee osteoarthritis symptoms and leg strength . Telehealth has also been investigated by means of a pilot study for physical therapy for partial rotator cuff injury . Other studies have looked at telehealth in follow‐up after joint arthroplasty and following fractures and found that overall home telehealth is at least as effective as usual care .…”
Section: Specific Telehealth Applications For Neuromuscular or Musculmentioning
confidence: 99%
“…58 Telehealth has also been investigated by means of a pilot study for physical therapy for partial rotator cuff injury. 64 Other studies have looked at telehealth in follow-up after joint arthroplasty and following fractures [65][66][67][68][69][70][71] and found that overall home telehealth is at least as effective as usual care. 69 A systematic review of telehealth for physiotherapy after orthopedic surgery found "strong evidence in favor of telehealth in patients following total knee and hip arthroplasty."…”
Section: Specific Telehealth Applications For Neuromuscular or Musculmentioning
confidence: 99%
“…In sports medicine, telehealth can be effective for management of musculoskeletal conditions including physical therapy and review of diagnostic imaging studies. Telehealth has been used for delivery of physical therapy services with a recent pilot study assessing telehealth services for rotator cuff injury [62]. Diagnostic imaging review between provider and patient of previous physical examination findings can be readily conducted via telehealth.…”
Section: Outpatient Musculoskeletal Care and Sports Medicinementioning
confidence: 99%
“…Such platform is an interactive environment that provides patients with access to a set of rehabilitation resources, such as education on the pathology, injury care, joint hygiene, activity modification and therapeutic exercises. This platform is currently undergoing clinical trials [74]. Finally, we found some news about the implementation of VirtualRehab, a commercial Ki-nect®-based platform for physical therapy supported by exergames.…”
Section: Méxicomentioning
confidence: 99%